Therapeutic Effects of BRC Functional Food from Indonesian Black Rice on Body Weight and Haematological Parameters in Obese Rats - Sofyantoro, Fajar; Syam, Adi Mazdi; Adania, Baik Aisyah; Almunawar, Muhammad Fikri; Nasution, Nurlita Putri Bela; Hidayat, Rheina Faticha Asyamsa; Mataram, Made Bagus Auriva; Maharesi, Chesa Ekani; Nurhidayah, Septika; Purwestri, Yekti Asih; Nuriliani, Ardaning; Hidayati, Lisna; Pratiwi, Rarastoeti (Journal of Tropical Biodiversity and Biotechnology, 2024)
Obesity increases the risk of various diseases. Black rice, renowned for its high anthocyanin content, is considered a potential functional food for preventing metabolic disorders. The current study investigated the effects of black rice crunch (BRC) on body weight and haematological profiles in obese rats. Rats were fed with high-fat diet to induce obesity and supplemented with different concentrations of BRC for 4 and 8 weeks. The results showed that high-fat diet effectively induced obesity, as evidenced by significant increase in body weight. Importantly, 75% BRC supplementation resulted in significant weight reduction in obese rats. Further analysis revealed an increase in erythrocyte numbers in obese groups supplemented with 75% BRC, but no significant changes in haemoglobin concentration or haematocrit percentage. Further investigation showed that 75% BRC led to a decrease in mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), and mean corpuscular volume (MCV), potentially affecting the size and concentration of haemoglobin within erythrocytes. The total leucocytes count increased with the high-fat diet, while BRC supplementation alone did not have significant impact. Lymphocyte percentage remained stable across the groups, indicating minimal influence of the dietary interventions. Neutrophil percentage varied initially but was not specific to BRC or the high-fat diet. Platelet count and distribution width were not significantly influenced, but mean platelet volume (MPV) increased after 8 weeks of BRC treatment, suggesting larger platelet sizes associated with obesity. Overall, the study provides important insights into the effects of BRC supplementation on body weight and haematological parameters related to obesity.